Research on the Cross Section Forming Quality of Three-Dimensional Multipoint Stretch Forming Parts - Jiaqi Yu; Yi Li; Fei Teng; Jicai Liang; Xiangfeng Lin; Ce Liang; Guangyi Chen; Guangping Sun (Advances in Materials Science and Engineering)
This paper introduced the basic principle and main influencing factors of the three-dimensional multipoint stretch forming process and investigated the optimized scheme of the cross section forming quality. The main factors affecting the stretch forming process were studied by the orthogonal test through the numerical simulation technique. In the case of a good target shape, the best combination of forming parameters was established by using the range method. The cross-sectional distortion of the formed profile is the smallest when the prestretching amount is 1% of the profile length, the poststretching amount is 0.8% of the profile length, the number of the die heads is 12, and the friction coefficient is 0.15. The optimal combination of forming parameters was verified by the multipoint bending test.